Effectiveness of Differentiated Digital Student Worksheets Based on Socio-Scientific Issues to Improve Students’ Science Literacy - Qalfin, Moh.; Saptono, Sigit; Ellianawati, Ellianawati; Novi Ratna Dewi (Universitas Negeri Semarang, 2024)
The purpose of the study was to determine the effectiveness of differentiated digital student worksheets based on socioscientific issues to improve students’ science literacy. The research employed a quasi-experimental design. The population was all students of class VII MTs N 1 Purbalingga in the 2023/2024 academic year. The sample was taken using the cluster random sampling technique and class VII A was selected as the experimental class and class VII D as the control class. The data collection instrument used a science literacy test. The data analysis technique in this research was carried out using quantitative description. The results of the research show that digital student worksheets are proven to be effective in increasing scientific literacy as seen from the average N-gain in the experimental class of 0,582 in the moderate category, higher than the control class of 0,323 in the moderate category. The results of the independent sample t-test are 0,001 < 0,05, which means there is a significant difference in increasing scientific literacy between the experimental and control classes. It can be concluded that SSI-based differentiated digital student worksheets are effective in increasing the scientific literacy of junior high school students.